The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1136/bmj.c912
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and risk of liver cirrhosis in middle aged UK women: prospective study

Abstract: Objective To determine the relation between body mass index (BMI) and liver cirrhosis and the contribution that BMI and alcohol consumption make to the incidence of liver cirrhosis in middle aged women in the UK. Design Prospective cohort study (Million Women Study). Setting Women recruited from 1996 to 2001 in NHS breast screening centres and followed by record linkage to routinely collected information on hospital admissions and deaths. Participants 1 230 662 women (mean age 56 years at recruitment) followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(169 citation statements)
references
References 18 publications
(17 reference statements)
11
155
2
1
Order By: Relevance
“…[1][2][3][4] The liver is a key visceral organ that is affected by ectopic fat accumulation, 1,2 and when excess body weight is present, the incidence of cirrhosis is markedly increased. 5,6 When liver fat accumulation >5% occurs that is not caused by excessive alcohol consumption or other known pathogenic factors, the presence of liver fat defines nonalcoholic fatty liver disease (NAFLD).…”
Section: Please See Http://atvbahajournalsorg/site/misc/ Atvb_in_fomentioning
confidence: 99%
“…[1][2][3][4] The liver is a key visceral organ that is affected by ectopic fat accumulation, 1,2 and when excess body weight is present, the incidence of cirrhosis is markedly increased. 5,6 When liver fat accumulation >5% occurs that is not caused by excessive alcohol consumption or other known pathogenic factors, the presence of liver fat defines nonalcoholic fatty liver disease (NAFLD).…”
Section: Please See Http://atvbahajournalsorg/site/misc/ Atvb_in_fomentioning
confidence: 99%
“…Given that patients in HES-linked practices are representative of the whole CPRD population and the latter is broadly similar in terms of demographics to that of England, we believe we have a representative population ( 10,16 ). Our defi nition of cirrhosis in secondary care, compared with that used by other studies, which included codes for chronic hepatitis and alcoholic liver disease ( 4,17 ), ensures that we are only including patients who have good evidence of cirrhosis. Although we have assigned a diagnosis date as the incident date of disease in our study (so as to be able to calculate rates of occurrence from a defi ned denominator), we appreciate that given the long sojourn time for cirrhosis to develop this will not be the onset of disease.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…2,18,19 In brief, it is a prospective cohort study that recruited 1.3 million women (mean age, 56.1 years) between 1996 and 2001, through the National Health Service (NHS) Breast Screening Pro-gramme in England and Scotland. At recruitment, women completed a questionnaire that enquired about current weight and height, use of hormone replacement therapy, smoking status, physical activity, alcohol consumption, medical and reproductive history, history of oral contraceptive use, and educational attainment (questionnaire available from www.millionwomenstudy.org).…”
Section: Study Populationmentioning
confidence: 99%
“…22 Incidence rates for the complete cohort were subsequently reported with the mean measured values for each body mass index category by use of methods described previously. 19 Million Women Study participants were excluded from the present analysis if they reported a history of blood clots or treatment for clotting problems at recruitment; or if, before recruitment, they had a hospital admission for venous thromboembolism (see online-only Data Supplement Appendix for International Classifications of Diseases codes), had surgery in the previous 12 weeks, or had a previous cancer registration (excluding nonmelanoma skin cancer). Women were classified as having had surgery during follow-up if the hospital data included 1 or more Classification of Surgical Operations and Procedures of the Office of Population Censuses and Surveys, fourth revision, codes (other than those related to the diagnosis and treatment of venous thromboembolism and those identified as nonoperative procedures in NHS coding guidelines, 23 as listed in the online-only Data Supplement Appendix).…”
Section: Study Populationmentioning
confidence: 99%